MCP extensors respond faster than flexors in individuals with severe-to-moderate stroke-caused impairment: Evidence of uncoupled neural pathways - Kim, Dongwon; Baghi, Raziyeh; Koh, Kyung; Zhang, Li-Qun (Frontiers in Neurology, 2023)
Damage in the corticospinal system following stroke produces imbalance between flexors and extensors in the upper extremity, eventually leading to flexion-favored postures. The substitution of alternative tracts for the damaged corticospinal tract is known to excessively activate flexors of the fingers while the fingers are voluntarily being extended. Here, we questioned whether the cortical source or/and neural pathways of the flexors and extensors of the fingers are coupled and what factor of impairment influences finger movement. In this study, a total of seven male participants with severe-to-moderate impairment by a hemiplegic stroke conducted flexion and extension at the metacarpophalangeal (MCP) joints in response to auditory tones. We measured activation and de-activation delays of the flexor and extensor of the MCP joints on the paretic side, and force generation. All participants generated greater torque in the direction of flexion (p = 0.017). Regarding co-contraction, coupled activation of the extensor is also made during flexion in the similar way to coupled activation of the flexor made during extension. As opposite to our expectation, we observed that during extension, the extensor showed marginally significantly faster activation (p = 0.66) while it showed faster de-activation (p = 0.038), in comparison to activation and de-activation of the flexor during flexion. But movement smoothness was not affected by those factors. Our results imply that the cortical source and neural pathway for the extensors of the MCP joints are not coupled with those for the flexors of the MCP joints.